A Survey on Cortical Bone Trajectory for Spinal Fusions - Sedighi, Amirsaeed; Zali, Ali Reza; Seddighi, Afsoun; Beheshtian, Maryam Sadat; Sheykhi, Seyed Ali Reza; Ommi, Davood; Naimian, Shoeib; Yourdkhani, Fatemeh; Tabatabaei, Mahmood (International Clinical Neuroscience Journal, 2016)
There have been a number of developments in screw design and implantation techniques over recent years, including proposal of an alternative trajectory entitled as cortical bone trajectory (CBT). Cortical bone trajectory has been investigated in recent medical treatments as an alternative for screw fixation aimed at increasing purchase of pedicle screws in higher density bone. CBT screw insertion follows a lateral path in the transverse plane and caudocephalad path in the sagittal plane. This technique has been advocated because it is reportedly less invasive, improves screw−bone purchase and reduces neurovascular injury. Furthermore CBT pedicle screw fixation provides stabilization to multilevel lumbar segment with low-grade spondylolisthesis comparable to the standard trajectory pedicle screw construct. However, these claims have not been supported by robust clinical evidence. Recent investigations focus on evaluations of CBT as a pioneer method.